Extralevator Abdominoperineal Excision (ELAPE) is Not Superior to Abdominoperineal Excision (APE) in the Era of Neoadjuvant Treatment in Rectal Cancer - Ulusoy, Cemal; Nikolovski, Andrej (Macedonian Academy of Sciences and Arts / Sciendo, 2022)
Aim: To evaluate the effect of extralevator abdominoperineal excision of the rectum (ELAPE) on the circumferential resection margin (CRM) and overall survival in comparison to standard abdominoperineal excision of the rectum (APE) in patients with advanced rectal cancer. Material and Methods: This retrospective study encompasses patients with advanced rectal cancer operated on with two different methods: prone Jack-Knife position ELAPE and APE. In part of them, neoadjuvant chemoradiation was conducted. Postoperative patient, tumor, and outcome data were analyzed in terms of differences in CRM positivity and overall survival. Results: Of 67 patients treated with either APE (52) or ELAPE (15), 43 were male and 24 were female. Neoadjuvant treatment was conducted on 49 of the total patients. Complete pathological response (T0) was achieved in 3 patients. Positive CRM was reported in 7 patients (11.5 %), 3 in ELAPE and 4 in APE group (p = 0.348). The overall postoperative complication rate was 56.7%. Mean survival period was 42.2 months. Overall survival rate for both groups was 67.2 %. No statistical differences were seen between the ELAPE and APE procedure in terms of overall survival (p = 0.483). Conclusions: Differences between the use of ELAPE and APE in terms of CRM positivity and overall survival were not statistically significant. Therefore, we conclude that ELAPE is not superior to standard APE in the treatment of advanced rectal cancer.